Analisis Proses Penetapan Perkawinan Poligami pada Pengadilan Agama Larantuka, Kabupaten Flores Timur - Citra Rahmatul Ummah; Siti Ramlah Usman; Husni Kusuma Dinata (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
This study aims to analyze and find out the analysis of the process of determining polygamous marriage at the Larantuka Religious Court, East Flores Regency. This type of research is an empirical research that uses primary, secondary and tertiary data collected using interview techniques and literature studies and analyzed in a qualitative descriptive manner. The results of the study show that (1) The process of determining polygamous marriage consists of information services, case acceptance and trial activities (2) Factors that affect people not to apply for the determination of polygamy in religious courts, namely lack of knowledge, related to customs and complicated management.